PENYULUHAN KESEHATAN DAN PEMERIKSAAN KADAR GULA DARAH SEBAGAI UPAYA PENCEGAHAN DIABETES MELITUS DI DESA CURAH COTTOK, SITUBONDO - Astarini, Made Indra Ayu; Maryuti, Ira Ayu; Pae, Kristina; Mare, Agustina Chriswinda Bura (Fakultas Bisnis, Universitas Katolik Widya Mandala Surabaya, 2024)
Diabetes mellitus is a disease whose population is increasing and can occur at all ages. This disease generally appears in the elderly. Diabetes mellitus is characterized by increased glucose levels in the blood. In rural communities, knowledge about this disease is still minimal, so hyperglycemia is usually only discovered when the condition gets worse. Blood sugar levels can be determined through blood sugar checks. The people in Curah Cottok Village have a pattern of consuming quite a lot of sugar. Drinks tend to taste very sweet when consumed. Apart from that, this village also produces crackers where the basic ingredient for making crackers is flour which is another source of carbohydrates. This needs to be watched out for because it can be a factor in increasing blood sugar levels. Increasing community knowledge in rural areas is carried out through health education activities and health consultations. Early detection of diabetes mellitus is carried out through random blood sugar level checks. This community service activity was carried out in Curah Cottok Village, Situbondo. Participants in this activity were 26 people aged 50-80 years. The result of this community service activity is a change in the village community's knowledge from knowing to knowing about diabetes mellitus and the prevention that needs to be done. Another result is data reports on residents who are at risk of developing diabetes mellitus. This data can be used by village officials or village midwives to plan referrals to health facilities or programs to prevent diabetes mellitus complications